Classical mechanics - Upadhyaya, J. C. (Mumbai: Himalaya Publishing House, 2005)
Present book deals with an advanced course on mechanics, namely classical mechanics, for the students of B.Sc., M.Sc and B.E. classes. In addition to a course book, it has been written for the candidates, struggling to qualify competitive examinations at national and state levels as NET, GATE, I.A.S. etc.
Index 477-480p.
Keywords: Classical mechanics; Mathematics; General Science